Teacher opinions on school improvement and professional development - YILMAZ VİRLAN, AYŞE (My University, 2022)
This study aimed to provide the administrators and teachers with insights, along with the strengths and weaknesses, of instructor evaluation via the perceptions of English instructors for school improvement. The study employed the Utilized Focused Evaluation as its framework. Data were collected through a mixed method design, including a questionnaire and interviews. The results revealed that the instructor evaluation process has a positive effect on teacher professional development and school improvement. The findings indicate that to make instructor evaluation more useful, improvements should be made to classroom observation procedures and more time should be allocated for teacher professional development by the administrators.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Social Sciences and Humanities; Education; Educational Sciences; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Learning Leadership; Instructor Evaluation; School Improvement; Professional Development